2022
DOI: 10.3390/app12136790
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Behavior Detection Based on Improved YOLOv5 Algorithm Combining Multi-Scale Feature Fusion and Attention Mechanism

Abstract: The detection of students’ behaviors in classroom can provide a guideline for assessing the effectiveness of classroom teaching. This study proposes a classroom behavior detection algorithm using an improved object detection model (i.e., YOLOv5). First, the feature pyramid structure (FPN+PAN) in the neck network of the original YOLOv5 model is combined with a weighted bidirectional feature pyramid network (BiFPN). They are subsequently processed with feature fusion of different scales of the object to mine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…The original YOLOv4 was compared with an improved network (PANet and Faster R-CNN), and the results showed that the enhanced network can achieve better results and is suitable for student detection and recognition tasks. Tang et al [24] presented a classroom behavior detection algorithm based on an improved YOLOv5 object detection model. They combined a weighted bidirectional feature pyramid network (BiFPN) with the feature pyramid network and the path aggregation network (FPN+PAN) structure of YOLOv5.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The original YOLOv4 was compared with an improved network (PANet and Faster R-CNN), and the results showed that the enhanced network can achieve better results and is suitable for student detection and recognition tasks. Tang et al [24] presented a classroom behavior detection algorithm based on an improved YOLOv5 object detection model. They combined a weighted bidirectional feature pyramid network (BiFPN) with the feature pyramid network and the path aggregation network (FPN+PAN) structure of YOLOv5.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address the limitations of CNN-based target detection methods, their system employs a feature pyramid structure and the CARAFE lightweight operator to process multi-scale feature maps effectively and enhance the network's detection accuracy. This system achieved a significant 6.1% improvement in detection accuracy compared with the original deformable DETR model and outperforms Faster R-CNN, SSD, and YOLOv3 [21], v5 [24], and v7 [25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Perkembangan metode YOLO juga sangat cepat terhitung sejak dua tahun terakhir sudah terdapat versi yang ke-7 [15]. Selain perkembangan YOLOv7 terdapat kustomisasi YOLO yang lain seperti FMD-YOLO [16], ETL-YOLO [17], Modified YOLOv5 [18], Modified YOLOv4 [19] [20]. Selain penggunaan YOLO…”
Section: Pendahuluanunclassified
“…They analyzed classroom scenario characteristics and the technical intricacies of each module (task), offering baseline comparisons with mainstream datasets. Tang et al ( 2022 ) manually constructed a classroom teaching behavior detection dataset based on real classroom videos. Their dataset includes four behavior types: listening, looking down, lying down, and standing.…”
Section: Dataset Construction For Classroom Teaching Analysismentioning
confidence: 99%